The impact of land surface temperatures on suprapermafrost groundwater on the central Qinghai-Tibet Plateau - Huang, Kewei; Dai, Junchen; Wang, Genxu; Chang, Juan; Lu, Yaqiong; Song, Chunlin; Hu, Zhaoyong; Ahmed, Naveed; Ye, Renzheng (Hydrological Processes, 2020)
To investigate the influences of land surface temperatures (LSTs) on suprapermafrost groundwater discharge, a river valley was selected in a typical permafrost region of Fenghuoshan (FHS) watershed on the central Qinghai-Tibet Plateau. We developed a two-dimensional model to simulate the suprapermafrost groundwater seasonal dynamics controlled by LSTs and the changing trends under a warming climate scenario (3 degrees C/100 year). We calibrated key parameters of our model by the field observations at FHS watershed and analysed the relationship between the different LSTs and the suprapermafrost groundwater discharge dynamics in the active layer. The results show that (a) by changing the permeability of the active layer, the LSTs have a significant effect on the suprapermafrost groundwater discharge. A higher LST causes more suprapermafrost groundwater discharge, resulting in a different discharge pattern and affecting the ability to replenish the nearby river in the permafrost area. (b) Under a warming climate, the most obvious change in the suprapermafrost groundwater occurs in the freeze initiation period (from October to December), and there is a significant increase in the suprapermafrost groundwater discharge rate. This study reveals that the LST has a controlling effect on the seasonal dynamics of shallow groundwater systems in permafrost regions, indicating that the impact of local topography on the suprapermafrost groundwater should not be ignored in suprapermafrost groundwater simulations. Moreover, the warming simulation results demonstrate that the freezing season is the significant transformation period of suprapermafrost groundwater dynamics under future climate change, which can be used to better understand hydrological and ecological process changes in permafrost regions under climate warming.